Medicine As a Social Institution (Eurasian Scientific Herald, 2023)
Our article on the stability of the social system is based on the stability of social ties and relationships. The most stable social relations are institutional relations, that is, those that are connected within certain social institutions. A social institution is a set of status and roles, necessary material, cultural, and other means and resources aimed at performing a function of a certain social significance. According to modern ideas, the purpose of medicine is to enable people to live as socially full human beings in society. This goal, in turn, is achieved by creating certain methods of interaction between professionals with the necessary skills through training in the structure of culture as a whole, i.e. within the repetitive groups of doctors established and functioning as a sociocultural institution of medicine.